1974
DOI: 10.1002/dev.420070307
|View full text |Cite
|
Sign up to set email alerts
|

Early experience, ultrasonic vocalizations, and maternal responsiveness in rats

Abstract: Following a 2-min exposure to 5-6"C, neonatal rats emit ultrasounds for about 5 min, resulting in effective maternal care. Five minutes of 5 6°C causes prolonged ultrasonic vocalizations and correlated agitation in the mothers. The nonlinear effects of variable intensities of neonatal stimulation appear to be related to these differences in maternal behavior.Experimental investigations of the effects of infantile stimulation upon subsequent development of mammals have been reviewed by Levine (1962), Schaefer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
3

Year Published

1976
1976
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 11 publications
2
36
0
3
Order By: Relevance
“…First, changes in maternal behavior can play a role, as we and others (Misanin et al, 1977) have found that foster mothers provide more maternal attention and stimulation to the pups than do the biological mothers. This mechanism has also been proposed to account for the long-term effects observed after other forms of neonatal stimulation (Bell et al, 1974;Hennessy et al, 1988). Second, changes in the hormonal status of the mother may be involved in the effects of adoption per se.…”
Section: Discussionmentioning
confidence: 97%
“…First, changes in maternal behavior can play a role, as we and others (Misanin et al, 1977) have found that foster mothers provide more maternal attention and stimulation to the pups than do the biological mothers. This mechanism has also been proposed to account for the long-term effects observed after other forms of neonatal stimulation (Bell et al, 1974;Hennessy et al, 1988). Second, changes in the hormonal status of the mother may be involved in the effects of adoption per se.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the rodent dam is sensitive to the changing stimulus qualities of the pups (Meier and Schutzman, 1968;Young, 1965) and shows systematic changes in maternal behavior depending on the nature of the treatment that the offspring have received (Barnett and Burn, 1967;Bell et al, 1974) and the time during lactation in which the manipulations occur (Smotherman et al, 1977a, b). It has been demonstrated that heightened maternal behavior results from pup cues elicited by more intense treatments such as electric shock (0.4 mA) (Smotherman et al, 1977a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of an infant's formation of early life relationships and its social interactions with caretakers are known to last well in to adulthood with both beneficial and harmful effects [28,35,70]. In our laboratory, we study the development of social relationships between infant rats and their dams, sires, and littermates using an isolation, reunion, and re-isolation test paradigm.Infant rats emit ultrasonic vocalizations (USV) in a variety of situations, including as a response to isolation, physical manipulation, and thermal and olfactory challenge [1][2][3]6,19,25,46,79,80,82,97]. Many researchers have used the presence and absence of these sounds to make inferences about the internal state of the rodents, e.g., isolation-induced USV's have often been called "distress vocalizations" [29,76,78].…”
mentioning
confidence: 99%